Safety Management System – Hur kan rederiverksamheter tillse att reglerna för SMS inom ISM-koden uppfylls? - Areschoug, Niklas; Ahlbaum, Rebecca (My University, 2016)
International Safety Management Code, issued by the International Maritime Organization (IMO), introduces an international standard regarding the safe management and operation of ships and for pollution prevention. It is mainly found in SOLAS, which is a convention on maritime safety. Safety Management Systems, SMS, are safety management system’s that consists of all the essential policies, procedures and practices required to ensure safety at sea. All requirements in the ISM Code have to be met through SMS. The aim of this bachelor thesis is to describe how it is ensured that the rules regarding SMS in the ISM Code are met. In this study existing cases are being examined, and the differences which occurs are being investigated. The thesis consists of five research questions in total, which are being throughout the report. The method is based on a qualitative research where collection of data, two semi structured interviews and questionnaires, with five representatives from five separate sipping companies, have been used as the main source of information. A discussion is held on the results, to finally come up with a recommendation on how shipping companies can work towards regulatory improvement. Three methods for ensuring compliance with regulations were found; working towards checklists, relying on experience and to work towards regulatory frameworks in document form. The method of working towards checklists is being seen as the most beneficial since it is the most structured way. It also simplifies the work of the crew, since they often work on a rotating schedule. Further on the general picture of the ISM Code is being discussed to finally determine that a future restructuration of the framework might be a favorable solution for the general shipping industry.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics